(untitled) (Web of Teachers: Inderscience Research, 2025)
This article covers the application of speech action theory in pre-election speeches. What candidates say in public is treated not only as information, but as a pragmatic act with a certain power of influence. The role of speech acts such as promises, summons, thank you in political campaigns and the mechanism of their influence on the decision of the audience are analyzed in a simple and understandable way.